Applying an integrated engagement model to support country-led food systems transformation: Insights from the SHiFT Initiative's approach in Viet Nam, Ethiopia, and Bangladesh - Honeycutt, Sydney; Wyatt, Amanda; Lundy, Mark; Brouwer, Inge D. (International Food Policy Research Institute, 2025)
From 2022-2024, the CGIAR Research Initiative on Sustainable Healthy Diets through Food Systems Transformation (SHiFT) combined high-quality nutritional and social science research with development and policy partnerships to generate innovative food systems solutions that contributed to sustainable healthy diets. Through a country-led approach, SHiFT supported the design and implementation of national food systems transformation activities in Viet Nam, Ethiopia, and Bangladesh, aiming to achieve sustainable healthy diets while also working toward improved livelihoods, gender equity, and social inclusion. Following the 2021 United Nations Food Systems Summit (UNFSS), countries were encouraged to define pathways for transforming their food systems to align with the 2030 Agenda and Sustainable Development Goals (SDGs).2 Many countries have since developed national action plans to operationalize these pathways, requiring coordinated multisectoral efforts. SHiFT contributed to this process by generating evidence and supporting national stakeholders in developing context-specific food systems solutions. This brief introduces SHiFT’s country engagement strategy and explains how SHiFT supported collaborative pathways and processes in each target country during its initial phase. Consumers and Food Environments, Area of Work 1 in the new CGIAR Science Program on Better Diets and Nutrition, will build upon the SHiFT approach starting in 2025 through 2030.